O papel da Controladoria-Geral da União no Sistema de Integridade Brasileiro - Rico, Bruno Gabriel de Melo (2014)
Given that the fight against corruption in Democratic Law States depends greatly on the ability and cooperation between organs of the state itself to prevent unlawful acts, this research focuses on one of these institutions from the perspective of "checks and balances", trying to understand their role in the Web of Accountability Institutions of Brazil. Established in 2003 as an advisory body to the Presidency and composed of servers of the careers in internal control, CGU emerged relatively quickly in the Brazilian scene as a typical anti-corruption agency. With skills to prevent corruption, promote administrative accountabilities, ombudsman ( ouvidorias ) and internal control, this body had direct or indirect participation in deepening democratic control of the state activities. Among them include a significant increase of administrative sanctions under the federal executive branch, establishing systematic cooperation with other institutions of horizontal accountability, the contribution in the development of related laws, and participation in international forums. In this exhibition, apart from finding the main results achieved, we intend to understand how and why those results were obtained. We advocate the interpretation that, for this, CGU catalyzed previously existing devices, the main one being the new internal control system of the Federal Executive, which starts with the creation of the Federal Bureau of Internal Control (SFC) in 1994. CGU would instrumental part of these works to the topic discussed here, so that audits of internal control would subsidize the improvement of prevention, of administrative penalties and also of the investigative work of other bodies of horizontal accountability. In the last two chapters, we still problematize the seemingly unusual fact of an organ of internal control exercising such an important role in the role of checks and balances of the Brazilian State